MODEL ANALISIS WACANA KRITIS SARA MILLS DALAM MENGANALISIS REPRESENTASI GENDER DI MEDIA SOSIAL: STUDI KASUS PADA NARASI FEMINISME DALAM KONTEN DIGITAL 2024 - Oktapiyani, Deti; Hamdani, Agus (Universitas Sultan Ageng Tirtayasa, 2025)
This research focuses on the analysis of gender representation in feminist narratives on social media using the Critical Discourse Analysis (CDA) Model developed by Sara Mills. The background of the study is rooted in the growing influence of social media in shaping public perceptions of gender issues, where feminist discourse often intersects with patriarchal norms. The aim of the research is to identify the themes that emerge in digital content and to understand how feminist narratives contribute to gender representation. The research method employed is a qualitative approach with content analysis, where data is collected through surveys and interviews, and analyzed using critical discourse analysis techniques. The findings reveal five main themes: objectification, stereotype reinforcement, empowerment, rejection of norms, and diversity representation. The study concludes that although there is content that reinforces gender stereotypes, social media also offers a platform to introduce more inclusive and positive narratives. This research significantly contributes to the literature on discourse analysis and gender representation and paves the way for further studies on the relationship between media, gender, and society in the digital age. Keywords: Critical discourse analysis, gender representation, social media, feminism, digital content.